15. listopad 1939: Zprávy německé provenience - Michal V. Šimůnek (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
The mass demonstrations following the funeral of Jan Opletal, a student at the Faculty of Medicine of Charles University deadly wounded by the shot on 28 October 1939, in the centre of Prague on 15 November 1939, have remained rather in the shade of the brutal German aftermath two days later, on 17 November 1939. It has to be kept in mind that they had been the most overt Czech protest against the German occupation before May 1945. Their course was recorded contemporarily in both Czech and German official reports, which have been taken into account in the post-war historical literary production to certain degree. Those reports, unedited and unpublished so far, served on the German part as a basis for the key political decisions of criminal nature. Seven of such reports could be found and are presented in this edition. Among others, the report from the head of the Reich Main Security Office (Reichssicherheitshauptamt) R. Heydrich to the head of the Reich Chancellery (Reichskanzlei) H. H. Lammers from 15 November 1939 is published here for the very first time.